Incidence and risk factors for 30-day readmission in ulcerative colitis: nationwide analysis in biologic era. Issue 9 (September 2021) - Vohra, Ishaan; Attar, Bashar; Haghbin, Hossein; Mutneja, Hemant; Katiyar, Vatsala; Sharma, Sachit; Abegunde, Ayokunle T.; Demetria, Melchor; Gandhi, Seema
Abstract : Background and study aim: Ulcerative colitis (UC) is a chronic relapsing and remitting disease requiring frequent hospitalization. Biologics have become the recommended initial therapy for Biologics in patients with moderate to severe UC. Our aim was to estimate the changes in Nationwide Healthcare utilization and assess predictive factors of 30-day readmission, morbidity and mortality of UC. Methods: This is a retrospective observational study analyzing the Nationwide Readmission database from 2016 to 2017 using ICD-10 codes. The primary outcomes of the study were to assess the predictors of 30-day readmission in patients with UC. Results: Of the 54 138 adult patients with a primary diagnosis of UC, 13.2% were readmitted within 30 days of index hospitalization. The mortality rate (1.4 vs. 0.3%, P < 0.01), length of stay (7 vs. 4.9 days, P < 0.01) and hospital cost (62 552 vs. 46 971, P < 0.01) were higher on readmission as compared to index hospitalization. We identified multiple patient-related factors (age <65years, men, VTE, protein calorie malnutrition, electrolyte imbalance, anemia, anxiety and alcohol abuse), hospital-related factors (teaching hospitals, high quintile hospitals), as independent predictors of 30-day UC readmission. Colonoscopy, Cannabis use, and colectomy were associated with decreased odds of 30-day readmission. The most common cause of UC was septicemia. Conclusions: This is the largest nationwide study demonstrating predictors of 30-day readmission, mortality and morbidity associated with UC. Identification and amelioration of these risk factors will decrease readmission rate and mortality amongst UC patients. Abstract : Supplemental Digital Content is available in the text.